Estimation of the refractive indices of some binary mixtures (2015)
Refractive index is a useful fluid characterization parameter with widespread industrial applications. The value for many pure liquids are known or readily available in literature. However, when experimental literature are not available, the refractive indices of binary and multicomponent liquid are often estimated from the pure components using mixing rules which are sometimes not accurate. This study was designed to measure the refractive indices and evaluate the accuracy of some commonly used mixing rules when applied to benzene-toluene, heptane-hexane, hexane-acetone, heptane-acetic acid and acetic acid-acetone binary mixtures at varying volume fractions and temperatures between 20 and 60˚C. A simpler relation based on modified Kay or Arago-Biot mixing rule was demonstrated to have wider range of applicability because of the explicit temperature-dependence term.